2018
DOI: 10.5812/ijpbs.11255
|View full text |Cite
|
Sign up to set email alerts
|

Using Prototype Willingness Model to Predict Waterpipe Smoking among High School Adolescents in Birjand, Iran

Abstract: Background: While waterpipe tobacco smoking is associated with several health-related risks, its prevalence is on the rise among young age individuals, including high school adolescents. Social aspects related to waterpipe smoking comprise a major reason for the initial orientation to its consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
3
2
1
Order By: Relevance
“…In this study, the analysis of the social reaction path in PWM showed that attitudes, subjective norms and positive prototype of participants predict the willingness to SS. Besides, there is a positive and significant relationship between these structures and behavioral willingness, which is consistent with the findings of earlier studies 28,30,36 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the analysis of the social reaction path in PWM showed that attitudes, subjective norms and positive prototype of participants predict the willingness to SS. Besides, there is a positive and significant relationship between these structures and behavioral willingness, which is consistent with the findings of earlier studies 28,30,36 .…”
Section: Discussionsupporting
confidence: 92%
“…Various pathways have been identified as predictors of behavior. In some studies 30,40,42 , the behavioral intention has been introduced as an important predictor of behavior, which is consistent with the present study. However, other studies 28,32 reported behavioral willingness as a more important predictor of behavior.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to a comprehensive study, determinants of WP smoking in females include behavioral beliefs and attitudes 6 - 9 , subjective norms 7 , 10 - 12 , behavioral prototype 13 , 14 , behavioral willingness 7 , 13 , 14 and behavioral intention 15 - 18 .…”
Section: Introductionmentioning
confidence: 99%